Edukasi Aplikasi Mobile JKN pada Komunitas PEKKA Kota Pontianak: JKN Mobile Application Education in the PEKKA Community in Pontianak City - Masdah, Siti; Rizky, Ayu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Long queues to get health services are still a major obstacle for the community, which is exacerbated by the knowledge gap regarding the use of the Mobile JKN application. Many communities, especially the Women-Headed Household Empowerment (PEKKA) group, do not understand the benefits and how to use this application. This condition has an impact on the low quality of National Health Insurance (JKN) services. This community service activity aims to increase community knowledge and participation in the JKN program through education and practice of using the Mobile JKN application. The method used was lecture and hands-on practice. The material presented included activation procedures, application benefits, available features, and tutorials. The results of the activity showed an increase in the average knowledge of respondents from 55.1 to 77.3 after counseling. Most of the participants also managed to practice the use of the application features correctly. Increased use of this application facilitates and accelerates the health service administration process and increases user satisfaction. Hopefully, this information can be disseminated to the surrounding community so that more people can benefit from the Mobile JKN application.